Analisis Pemanfaatan E-book Sebagai Bahan Penunjang Pembelajaran Oleh Pengguna Perpustakaan SMAN 1 Kedungwaru Tulungagung - Arin Prajawinanti; Nita Khoirunnisa (THE LIGHT : Journal of Librarianship and Information Science, 2023)
Current technological advances lead us to rapid development. One of the developments that occurred was in the library. The information needs of library users are facilitated by the existence of e-books which can be used as learning support. . E-books are library materials in digital form which are considered as library materials that can be accessed whenever and wherever we need them. This research was conducted to find out how the use of e-book library materials as a support for learning at SMAN 1 Kedungwaru. The research method used in this study is qualitative and presented in a descriptive form using observation, interviews and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions/verification. The results of the study show that students at SMAN 1 Kedungwaru have used e-books as a learning support. They use e-books as reading material to add insight. This is considered a practical matter to obtain learning materials, especially during a pandemic. The existence of this e-book also has a big influence on student academic achievement. E-books are also considered to make it easier for students to fulfill academic information. The results of this study also show that there are still students who have not been able to make full use of e-books. What's more, the collections provided are still limited, so students choose to look for library materials in physical form. However, librarians try their best to add library materials and carry out promotions so that students can make the most of e-books. E-book library materials can be put to good use and are also effective in utilizing the facilities provided. The e-book is used as a reference in supporting the learning process. The suggestion of this research is the need for encouragement or motivation so that users can make the most of e-books.